The crisis of the Italian state from the origins of the Cold War to the fall of Berlusconi - McCarthy, Patrick 1941-2007 (St. Martin's Press, 1995)
The current governmental crisis in Italy is not a historical anomaly in that country, but rather just one more development in an evolving crisis of government that began with the close of World War II. As the Christian Democrats came to power, the hope of the Italian people was pinned on their promises for a renewed Italy. As time progressed, it became obvious that the trust of the people had been misplaced. In the first full English language account of the Clean Hands crisis, Patrick McCarthy finds the roots of Berlusconi's rise and fall in the practices of clientalism, the machinations of the Mafia, the corporate direction of Fiat, the edicts of the Vatican, and even the organization of the Italian soccer league. Showing how the tentacles of political corruption reached into every aspect of Italian life, Patrick McCarthy weaves a fascinating story that will be of great interest to any reader of current affairs.
Keywords: Geschichte 1900-2000; Geschichte 1945-1995; Binnenlandse politiek; Buitenlandse politiek; Außenpolitik; Politik; Politische Krise; Korruption; Klientelismus; Geschichte; Italien; Italy -- Politics and government -- 20th century